The Magical Fomula on a Lost Uterine Amulet - Gradvohl, Edina (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The article tries to reconstruct the inscription of a magical gem found in 1883 in Torontál which went lost by now. For this reconstructive work I used other gem inscriptions and also other magical papyri and lead tablets in order to compare the two types of texts. The inscription contains the Soroor-logos and the Gigantorekta barophita-logos as well. The gem and the inscription together were used for the protection of the uterus.